Literature Review : Application of Human Resources Accounting in the International World (Period 2019 to 2022) - Maisyarah, Renny; Nasution, Dito Aditia Darma; Wahyu, Ahmad Braja; Sijabat, Hotman D; Yani, Isbet; Azani, Namira; Syari, Meilya Evita (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research adopts a qualitative approach, moving away from hypothesis testing to focus on describing contemporary phenomena, examining historical contexts, and deepening our understanding of key variables. Secondary data serves as the foundation for this investigation. The research process begins with comprehensive data collection and analysis, drawing from diverse sources including scholarly literature, academic publications, textbooks, digital resources, and other relevant materials. Through a qualitative descriptive methodology, the researcher systematically gathers, arranges, and consolidates information to create a clear and detailed picture of human resource accounting practices in the international context.